1997
DOI: 10.1007/pl00006123
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Orthologous Retrovirus-Like Elements in the White-Footed Mouse, Peromyscus leucopus

Abstract: Three loci in the genome of the white-footed mouse, Peromyscus leucopus, were examined for the presence or absence of orthologous copies of the retrovirus-like element mys using polymerase chain reaction. We examined these loci in 28 mice collected throughout the P. leucopus species range. Mys insertions were present in only one of the individuals examined at the mys-1 and mys-7 loci. Conversely, the mys-6 element was found in several individuals, but the presence of this element was limited to northern latitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…If a mutation occurs in one of the LTRs, the 5' and 3' LTRs will no longer be identical. Over evolutionary time, as the 5' and 3' LTRs within a single element gradually diverge, the degree of sequence diver-gence between them can provide an estimate of the time that has elapsed since the element inserted (Jordan & McDonald 1998, 1999bSan Miguel et al 1998;Sawby & Wichman 1997;Stavenhagen & Robins 1988;Voytas & Boeke 1992). Third, an element can be excised from the genome owing to recombination between its 5' and 3' LTRs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…If a mutation occurs in one of the LTRs, the 5' and 3' LTRs will no longer be identical. Over evolutionary time, as the 5' and 3' LTRs within a single element gradually diverge, the degree of sequence diver-gence between them can provide an estimate of the time that has elapsed since the element inserted (Jordan & McDonald 1998, 1999bSan Miguel et al 1998;Sawby & Wichman 1997;Stavenhagen & Robins 1988;Voytas & Boeke 1992). Third, an element can be excised from the genome owing to recombination between its 5' and 3' LTRs.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have attempted to estimate the rates of Ty element transposition and excision in the laboratory (Curcio & Gar¢nkel 1991;Winston et al 1984). Furthermore, previous studies of LTRs have used sequence divergence within elements to estimate the age of elements in the genome (Jordan & McDonald 1998, 1999bSanMiguel et al 1998;Sawby & Wichman 1997;Stavenhagen & Robins 1988;Voytas & Boeke 1992). However, until now it has not been possible to determine the e¡ective rates at which these processes of transposition and excision have operated in nature over evolutionary time.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, any change between LTR of a single element will have occurred after the insertion of the element. On this basis, Sawby and Wichman (1997) showed that the time elapsed since individual elements transposed can be estimated from the nucleotide differences between the 5) and the 3) LTR of a retrotransposon. The average percent identity between the 5) and 3) LTRs of individual Ty1 and Ty2 elements is greater than 99 % for both families, whereas the percent identity among all LTRs of either group is significantly lower (around 91 and 97 % for Ty1 and Ty2 LTRs, respectively), suggesting that Ty1 and Ty2 have probably retrotransposed recently (Jordan and McDonald, 1998).…”
Section: Ty Retrotransposons Diversity and Evolutionmentioning
confidence: 99%
“…Additionally, evidence for recent activity of mys elements has been illustrated in the genus Peromyscus (Lee et al 1996;Sawby and Wichman 1997), and seemingly to be highly active in the lineage leading to the P. maniculatus/P. leucopus clade based on the rapid generation of different subfamilies (Lee et al 1996) with continued activity supported by the presence or absence of elements in orthologous loci of individual P. leucopus mice (Sawby and Wichman 1997). We therefore investigated mys elements in more detail, which yielded several surprising results.…”
Section: Discussionmentioning
confidence: 98%
“…The overarching objective of this investigation was to further explore the origins, expansion, and evolution of the novel mys family and potential subfamilies of LTR-retroelements of the understudied Cricetidae family of rodents (Wichman et al 1985), as the P. leucopus mys-1 element has been the only isolated full-length member with two nearly intact ORFs. Additionally, evidence for recent activity of mys elements has been illustrated in the genus Peromyscus (Lee et al 1996;Sawby and Wichman 1997), and seemingly to be highly active in the lineage leading to the P. maniculatus/P. leucopus clade based on the rapid generation of different subfamilies (Lee et al 1996) with continued activity supported by the presence or absence of elements in orthologous loci of individual P. leucopus mice (Sawby and Wichman 1997).…”
Section: Discussionmentioning
confidence: 99%